Influence of sputter power on structural and electrical properties of TiO2 films for Al/TiO2/Si gate capacitors. (15th May 2014) - Chandra Sekhar, M.; Nanda Kumar Reddy, N.; Venkata Rao, B.; Mohan Rao, G.; Uthanna, S.
<x xml:space="preserve">Abstract</x> Titanium dioxide (TiO2) thin films were deposited onto p‐Si substrates held at room temperature by reactive Direct Current (DC) magnetron sputtering at various sputter powers in the range 80–200 W. The as‐deposited TiO2 films were annealed at a temperature of 1023 K. The post‐annealed films were characterized for crystallographic structure, chemical binding configuration, surface morphology and optical absorption. The electrical and dielectric properties of Al/TiO2/p‐Si structure were determined from the capacitance–voltage and current–voltage characteristics. X‐ray diffraction studies confirmed that the as‐deposited films were amorphous in nature. After post‐annealing at 1023 K, the films formed at lower powers exhibited anatase phase, where as those deposited at sputter powers >160 W showed the mixed anatase and rutile phases of TiO2. The surface morphology of the films varied significantly with the increase of sputter power. The electrical and dielectric properties on the air‐annealed Al/TiO2/p‐Si structures were studied. The effect of sputter power on the electrical and dielectric characteristics of the structure of Al/TiO2/p‐Si (metal‐insulator‐semiconductor) was systematically investigated. Copyright © 2014 John Wiley & Sons, Ltd.